Blockchain and IoT integration : approaches and applications. - Kavita Saini (Boca Raton : CRC Press, 2022)
"IoT refers to the interconnection of smart devices and collect data and make intelligent decisions. It is embedded in everyday objects, enabling them to send and receive data. A lack of intrinsic security measures makes IoT vulnerable to privacy and security threats. Blockchain, an encrypted, distributed computer filing system designed to allow the creation of tamper-proof records. The merger of Internet of Things (IoT) and blockchain technology is a step towards creating a verifiable, secure and permanent method of recording data processed by "smart" machines. This book explores the platforms and applications of blockchain-enabled IoT"--
Includes bibliographical references and index.
Keywords: Blockchains (Databases); Internet of things